Regulatory simplification: the necessary distinction between regulating and administrative management - Muñoz Vicuña, Diego (2025)
Three bills are currently under discussion in the Chilean Congress, all with the common goal of simplifying regulation. These bills propose the creation of three agencies: (i) the Office of Sectoral Authorizations and Investment; (ii) the Committee of Undersecretaries for Regulation and Sectoral Evaluation; and (iii) the Agency for the Quality of Public Policies and Productivity.In light of these legislative proposals and the limited conceptualization of the subject, both nationally and internationally, this article aims to propose a conceptual framework for regulatory simplification, distinguishing between normative and administrative simplification, and offering recommendations for its more effective implementation.